Phosphatidylserine supplementation and recovery following downhill running - Kingsley, M. I.; Kilduff, L. P.; McEneny, J.; Dietzig, R. E.; Benton, D. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study investigated the effects of 750 mg of soybean-derived phosphatidylserine (S-PtdSer), administered daily for 7 d prior to a bout of eccentric exercise and for 2d following exercise, on delayed onset of muscle soreness and markers of muscle damage, inflammation, and oxidative stress that followed prolonged downhill running.